Creation of the Methodology of the Development of Functional Mathematical Literacy in the 8th Form of Mainstream School - Baranauskienė, Ingrida; Tomėnienė, Laima (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article deals with the aspects of the development of functional mathematical literacy of students with moderate special educational needs. Creating the methodology of the development of functional mathematical literacy of students with moderate special educational needs the action research was organized, where 9 eighth form students with moderate special educational needs, 9 parents of these students, 7 teachers of mathematics and 4 special educators participated. It has been found out that the development of functional mathematical literacy of students with moderate special educational needs educated in mainstream schools can be successfully organized when the methodology of its development is based on the combination of the concepts and theories of pragmatism, constructivism, social participation, empowerment, mathematical literacy, practical applicability of mathematical knowledge.